Pemberian Bisphenol A (BPA) Oral Menurunkan Kadar Superoksida Dismutase dan Meningkatkan Kadar F2-isoprostan pada Tikus Putih (Rattus norvegicus) Jantan Galur Sprague Dawley - Sulaiman, Yogie; Aman, IGM; Pangkahila, Wimpie (Jurnal Biomedik : JBM, 2017)
Abstract: Bisphenol A (BPA), commonly found in plastic packaging and cans, can induce oxidative stress. This study was aimed to prove that oral BPA could decrease superoxide dismutase (SOD) and increase F2-isoprostan levels in male Sprague Dawley rats. This was an experimental study using randomized pretest-posttest control group design. There were 14 rats (Rattus norvegicus), male, Sprague Dawley strain, 8-10 weeks old, as subjects. Rats were divided into two groups with 7 rats each. The control group (P0) was treated with placebo for 21 days and the treatment group (P1) was treated with oral BPA dose of 400mg/kg for 21 days. Before and after treatment for 21 days, blood was drained through the canthus medial sinus orbital and urine was collected as pretest and posttest data. SOD and F2-isoprostan levels were then examined by using ELISA. The results showed that before treatment (pretest), the mean SOD level in P0 group was 42.51±3.127 U/mL and in P1 group was 41.87±2.477 U/mL (P > 0.05). The mean F2-isoprostane level in P0 group was 3.18±0.599 ng/ml and in P1 group was 3.22±0.489 ng/ml (P > 0.05). However, after treatment for 21 days (posttest), the mean level of SOD in P0 group was 43.52±3.472 U/mL and in P1 group was 31.84±2.563 U/mL (P <0.01). The mean level of F2-isoprostane in P0 group was 2.94±0.500 ng/ml and in P1 group was 4.47±0.241 ng/ml (P < 0.01). The analysis of the treatment effect showed significant decreased level of SOD and increased level of F2-isoprostane in P1 group (P < 0.01). Conclusion: Oral bisphenol A could decrease superoxide dismutase (SOD) and increase F2-isoprostan levels in male Sprague dawley rats.Keywords: bisphenol A (BPA), SOD, F2-isoprostane, Sprague Dawley ratsAbstrak: Bisphenol A (BPA) banyak ditemukan dalam kemasan plastik dan kaleng dan dapat menyebabkan peningkatan radikal bebas. Penelitian ini bertujuan untuk membuktikan pemberian BPA oral dapat menurunkan kadar superoksida dismutase (SOD) dan meningkatkan kadar F2-isoprostan pada tikus (Rattus norvegicus) jantan galur Sprague Dawley. Jenis penelitian ialah eksperimental dengan randomized pretest-postest control group design yang menggunakan 14 ekor tikus (Rattus norvegicus) jantan, galur Sprague Dawley, berumur 8-10 minggu, yang terbagi menjadi 2 (dua) kelompok masing-masing berjumlah 7 ekor tikus. Kelompok kontrol (P0) diberikan plasebo selama 21 hari dan kelompok perlakuan (P1) diberikan BPA dosis 400mg/kgBB selama 21 hari. Sebelum dan sesudah perlakuan selama 21 hari, darah diambil melalui chantus medial orbitalis dan urin dikumpulkan untuk pemeriksaan pretest dan postest. Kadar SOD dan F2-isoprostan diperiksa dengan metode ELISA. Hasil penelitian menunjukkan bahwa sebelum perlakuan (pretest), rerata kadar SOD kelompok P0 42,51±3,127 U/mL dan kelompok P1 41,87±2,477 U/mL (P > 0,05). Rerata kadar F2-isoprostan kelompok P0 3,18±0,599 ng/ml dan kelompok P1 3,22±0,489 ng/ml (P > 0,05). Setelah perlakuan selama 21 hari (posttest), rerata kadar SOD kelompok P0 43,52±3,472 U/mL dan kelompok P1 31,84±2,563 U/mL (P < 0,01). Rerata kadar F2-isoprostan kelompok P0 2,94±0,500 ng/ml dan kelompok P1 4,47±0,241 ng/ml (P < 0,01). Analisis efek perlakuan menunjukkan terjadi penurunan kadar SOD dan peningkatan kadar F2-isoprostan yang bermakna pada kelompok P1 (P < 0,01). Simpulan: Bisphenol A oral dapat menurunkan kadar superoksida dismutase dan meningkatkan kadar F2-isoprostan pada tikus galur Sprague Dawley jantan.Kata kunci: BPA, SOD, F2-Isoprostan, tikus Sprague Dawley